COMMUNITY EMPOWERMENT REGARDING â€œONE HOUSE ONE JUMANTIKâ€ PROGRAM IN KARANG BESUKI SUB-DISTRICT, MALANG CITY - Alidha Nur Rakhmani; Lilik Zuhriyah; Rivo Yudhinata Brian Nugraha (Universitas Brawijaya, 2021)
In 2016, Indonesia has been launching the â€œIndonesia Sehat'' program which the strategy used is to strengthen health services through a family approach. According to the 2016 Ministry of Health technical guidelines, the larva inspector, also known as Juru Pemantau Jentik (Jumantik), is involved in Jumantik participating by each family. Their role is the same as 3M plus actions including in the inspection, monitoring, and eradication of mosquito larvae for controlling infectious diseases, especially Dengue Fever. The purpose of these activities was to increase community participation to conduct a â€œone house one Jumantik'' program. The study was the quasi-experimental post-test only design that was located in Karangbesuki sub-district, Malang City from August until September 2017. One cluster Rukun Warga (RW) from the Karangbesuki sub-district that consisted of 9 Rukun Tetangga (RT) was chosen as the location. The intervention was in collaboration with Mulyorejo Public Health Center (Pusat Kesehatan Masyarakat / Puskesmas) in Malang. The methods used were ovitrap utilization training and focus group discussion (FGD), health promotion and